Two switch three phase ĆUK regulated rectifier - Abedin, Amina Hasan; Choudhury, Mohammad Ali A.Shoukat (© 2016 IEEE, 2018)
This conference paper was published in the International Conference on Power System Technology, POWERCON 2016; Wollongong; Australia; 28 September 2016 through 1 October 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/POWERCON.2016.7754010 The Journal's website is at: https://ieeexplore.ieee.org/document/7754010/